Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1440-1754.2004.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of two dexamethasone regimens to reduce side‐effects in infants treated for chronic lung disease of prematurity

Abstract: The individualized course of dexamethasone used in this study reduced the total dose of dexamethasone administered but did not significantly reduce side-effects of treatment or alter outcome in infants at risk of chronic lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…Starting doses of DXM might have a greater effect on the integrity of the central nervous system than the cumulative doses of DXM. This hypothesis is supported by 2 randomized trials that reported comparable neurodevelopmental outcomes at 18 months between infants treated with similar starting doses (0.5 mg/kg/day) but different cumulative DXM doses [21,26]. …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Starting doses of DXM might have a greater effect on the integrity of the central nervous system than the cumulative doses of DXM. This hypothesis is supported by 2 randomized trials that reported comparable neurodevelopmental outcomes at 18 months between infants treated with similar starting doses (0.5 mg/kg/day) but different cumulative DXM doses [21,26]. …”
Section: Discussionsupporting
confidence: 60%
“…Although conclusive data on neurodevelopment are lacking [2,3,4,5,18,19,20], low-dose DXM treatment seems to be as effective as high-dose DXM treatment in weaning infants off the ventilator, lowering BPD rates, and in decreasing the total duration of supplemental oxygen [2,21]. The rate of BPD in our study, however, was high (94%) compared to previous studies on low-dose DXM, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Published and peer-reviewed full-text articles and abstracts in all languages were included. The characteristics of the included studies are provided in Table 1 . Studies that evaluated early-initiated dexamethasone (<8 days of postnatal age) or dexamethasone in established cases of BPD (≥28 days) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…16 However, 3 small individual RCTs that directly compared high versus low dexamethasone doses, variably defined, have revealed no differences in efficacy (Table 1). [17][18][19] These studies have generally been small and heterogeneous, which makes them difficult to compare.…”
Section: Literature Review Dexamethasonementioning
confidence: 99%